SKRINING KEHAMILAN SEBAGAI UPAYA PENINGKATAN KESEHATAN IBU HAMIL DI DESA YEH SUMBUL KECAMATAN MENDOYO KABUPATEN JEMBRANA: SKRINING KEHAMILAN SEBAGAI UPAYA PENINGKATAN KESEHATAN IBU HAMIL DI DESA YEH SUMBUL KECAMATAN MENDOYO KABUPATEN JEMBRANA - ni made ayu wulandari; Indrie Lutfiana; Ni Made Karlina Sumiari Tangkas (MIDWINERSLION : Jurnal Kesehatan STIKes Buleleng, 2022)
ABSTRACT The causes of maternal mortality are still high, which are influenced by delays in recognizingdanger signs in pregnant women, delays in reaching and making decisions to health facilities, age factors,delays in handling emergencies, limited level of education for pregnant women and knowledge. An earlypregnancy check is needed which is the first step in a prenatal check-up to identify any abnormalities orcomplications that may occur during pregnancy, and ensure the health of the mother and fetus. Efforts thatcan be made to prevent maternal and fetal morbidity and mortality provided by health workers are throughpromotive, preventive, curative and rehabilitative screening. The purpose of this study was to improve thehealth of pregnant women through pregnancy screening including pregnancy check-ups, examination of Hblevels as well as health education about anemia and Caloric Energy Deficiency (KEK) and danger signs inpregnancy. The research method is descriptive with a cross-sectional approach and community participationto get an overview of the health and knowledge of pregnant women about anemia in pregnancy and KEK anddanger signs of pregnant women. The target is 34 pregnant women, where the activity is in Yeh Sumbul village,Mendoyo District, Jembrana Regency from September to November 2021. The results of the examination ofpregnant women are mostly not anemia, 2 pregnant women (KEK) and 1 hypertension. After counseling,knowledge about anemia was good (50%), danger signs in pregnancy were good (97%). Screening for pregnant women can detect early health of mothers and babies, prevent and provide early treatment as well asprovide education. Health promotion and provide an overview of increasing knowledge of pregnant women.Key words: pregnant women, knowledge, screening